Mechanisms of Kidney Injury in Lupus Nephritis – the Role of Anti-dsDNA Antibodies - Yung, Susan; Chan, Tak Mao (Frontiers in Immunology, 2015)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by a breakdown of self-tolerance, production of auto-antibodies and immune-mediated injury, resulting in damage accrual in multiple organs. Kidney involvement, termed lupus nephritis, is a major cause of morbidity and mortality that affects over half of the SLE population during the course of disease. The etiology of lupus nephritis is multifactorial and remains to be fully elucidated. Accumulating evidence suggests that, in addition to forming immune complexes and triggering complement activation, anti-dsDNA antibodies contribute to the pathogenesis of lupus nephritis through binding, either directly or indirectly, to cross-reactive antigens or chromatin material respectively, to resident renal cells and/or extracellular matrix components, thereby triggering downstream cellular activation and proliferation, and inflammatory and fibrotic processes. Several cross-reactive antigens that mediate anti-dsDNA antibody binding have been identified such as annexin II and alpha-actinin. This review discusses the mechanisms through which anti-dsDNA antibodies contribute to immuno-pathogenesis in lupus nephritis. Corticosteroids combined with either mycophenolic acid or cyclophosphamide is the current standard of care immunosuppressive therapy for severe lupus nephritis. This review also discusses recent data showing distinct effects of mycophenolic acid and cyclophosphamide on inflammatory and fibrotic processes in resident renal cells.